1964
DOI: 10.1063/1.1725219
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis of Simple Aromatics in Boric Acid Glass

Abstract: Electron paramagnetic resonance studies have been made of the stable free radicals produced by x irradiation of aromatic hydrocarbons dissolved in partially dehydrated boric acid glass. In general, singly charged molecular ions were not found to be the sole species. Deuterium substitution in the boric acid glass showed that all end point radicals contained hydrogen from the matrix. All glasses exhibited a 100–140 G EPR pattern, which has been interpreted as that of radicals produced by formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
1981
1981

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The seven approximately equidistant lines are centered at g= 2.0022±0.0002 and are separated by 4.4 G. The outermost line on the high-field side is barely resolvable. Hughes et al 4 reported the spectra from resolution and the asymmetry may be due to a broader singly charged aromatic ions after x irradiation of background possibly from phenyl and cyclohexadienyl hydrocarbons in a boric acid glass. The relative amplitudes deviate from those expected for six equivalent protons due to the difference in linewidth; the M[=O line is symmetric and narrow, the outer lines become progressively more asymmetric.…”
Section: The Swedish Research Collncils' Laboratorymentioning
confidence: 99%
“…The seven approximately equidistant lines are centered at g= 2.0022±0.0002 and are separated by 4.4 G. The outermost line on the high-field side is barely resolvable. Hughes et al 4 reported the spectra from resolution and the asymmetry may be due to a broader singly charged aromatic ions after x irradiation of background possibly from phenyl and cyclohexadienyl hydrocarbons in a boric acid glass. The relative amplitudes deviate from those expected for six equivalent protons due to the difference in linewidth; the M[=O line is symmetric and narrow, the outer lines become progressively more asymmetric.…”
Section: The Swedish Research Collncils' Laboratorymentioning
confidence: 99%